Balancing enjoyment and learning in teaching software project management with game-based learning - Alf Inge Wang; Vegard Aas Knutsen; Eivind Askestad (Computers and Education Open)
Despite advancements in project management education, project failures remain common, often due to insufficient experience and skills. Games offer a valuable platform for teaching practical project management skills, allowing players to learn from mistakes without significant economic costs. However, many serious games in this field lack focus on engagement and motivation. The ''Software Project Management Game'' introduced in this article addresses these issues by incorporating motivational game design principles, drawing inspiration from entertainment games like Game Dev Tycoon and The Sims. The game ensures a smooth flow without unnecessary interruptions, putting players in control. Players progress through five projects of increasing complexity, gradually developing their skills and learning soft skills and task dependencies. This article details the design, implementation, and evaluation of the game, focusing on gameflow, intrinsic motivation, perceived learning, and usability. The results indicate that the game successfully balances enjoyment and learning, making it an effective tool for teaching core project management skills.